Consumo de pescado e riscos da presença de fármacos no ambiente aquático: um estudo na Baixada Santista – SP, Brasil - Frank, Mariana Caltabiano [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Pharmaceuticals play a crucial role in society, both in disease treatment and in improving longevity and quality of life. However, the improper disposal of pharmaceutical residues, which are often not fully metabolized, contributes to environmental pollution. Wastewater treatment plants are the main sources of pharmaceuticals and their metabolites in the aquatic environment, although improper disposal is also relevant. In Baixada Santista, on the coast of São Paulo, medication contamination is a significant environmental challenge. In this study, a bibliographic survey was conducted using databases of scientific articles and repositories of theses and dissertations from various universities; searches for publications using the descriptors "pharmaceuticals," "fish," and "environmental contamination" resulted in 36 works; when including "Baixada Santista," there were 7 publications remaining. The study on fish highlighted its nutritional value and importance to health as a significant source of proteins, vitamins, and omega-3 fatty acids. In Brazil, the average fish consumption is approximately 9 kg per person per year, with fishing in Baixada Santista being predominantly artisanal, with species such as sardine, shrimp, and croaker being prominent. Therefore, despite the health benefits provided by fish consumption, food safety must consider the presence of contaminants. Adequate risk management is essential to ensure consumption safety, considering the nutritional and economic importance of fish.

Os fármacos desempenham um papel crucial na sociedade, tanto no tratamento de doenças quanto na melhoria da longevidade e qualidade de vida. Entretanto, a disposição inadequada dos resíduos de fármacos, que muitas vezes não são totalmente metabolizados, contribui para a poluição ambiental. As estações de tratamento de esgoto são as principais fontes de fármacos e seus metabólitos no ambiente aquático, embora o descarte inadequado também seja relevante. Na Baixada Santista, litoral de São Paulo, a contaminação por medicamentos é um desafio ambiental significativo. Neste estudo, foi realizado um levantamento bibliográfico utilizando bases de dados de artigos científicos e repositórios de teses e dissertações de várias universidades, as buscas por publicações usando os descritores "fármacos", "pescado" e "contaminação ambiental" resultou em 36 trabalhos; ao incluir "Baixada Santista", restaram 7 publicações. O estudo sobre o pescado ressaltou seu valor nutricional e sua importância para a saúde como uma fonte importante de proteínas, vitaminas e ácidos graxos ômega-3. No Brasil, o consumo médio de peixe é de aproximadamente 9 kg por pessoa por ano, com a pesca na Baixada Santista sendo predominantemente artesanal, destacando-se espécies como sardinha, camarão e corvina. Portanto, apesar dos benefícios à saúde proporcionados pelo consumo de peixes, a segurança alimentar deve considerar a presença de contaminantes. É imprescindível uma gestão de riscos adequada para garantir a segurança do consumo, considerando a importância nutricional e econômica do pescado
Fish Consumption and Risks of Pharmaceuticals Presence in the Aquatic Environment: A Study in the Baixada Santista – SP, Brazil
Keywords: Ecotoxicologia aquática; Contaminante emergente; Contaminação ambiental; Consumo de pescado; Segurança alimentar; Resíduos químicos